The effect of internationalization, industrial type, and company size on corporate social responsibility disclosure - Frista Frista; Kenny Fernando (Jurnal Siasat Bisnis, 2020)
The Multinational Companies has been internationally connected to the world where transparency and accessible information about economic, social, and environment are ultimately required. This study aims to determine the factors that affect the level Corporate Social Responsibility Disclosure (CSRD) by examining the effect of internationalization, industry type, and company size. The samples used are manufacturing companies listed on the BEI during 2013-2015. Data obtained from the company's annual reports. This research uses a quantitative approach with multiple linear regression analysis. On the other side, the researchers also use internalization instead of foreign ownership which existing researches mostly use. In addition, it distinguishably uses NVIVO Software in measuring CSRD instead of scoring to decrease subjectivity. This study shows that the size of firm has a positive effect on the CSRD. There is no evidence of internationalization and industry type effect on the level of CSRD in Indonesia.